Synchronous crustal growth and reworking recorded in late Paleoproterozoic granitoids in the northern Tarim craton: In situ zircon U-Pb-Hf-O isotopic and geochemical constraints and tectonic implications - Ge, R.; Zhu, W.; Wilde, Simon; He, J.; Cui, X. (Geological Society of America, 2015)
Identifying the relative contribution of various crustal and mantle materials in the source of granitoids is crucial for the study of granite petrogenesis and crustal growth. Extensive and diverse late Paleoproterozoic metamorphosed granitoids are exposed in the western Kuruktag block, northern Tarim craton, marking an important tectonothermal event. Here, we report sensitive high-reso lution ion microprobe (SHRIMP) and laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) zircon U-Pb ages, in situ zircon Hf-O isotopic data, and whole-rock geochemical data for a variety of granitoids, including monzogranite, quartz diorite/quartz monzonite, garnet-bearing granodiorite, tonalite, and trondhjemite. Geochronological data show that all these granitoids were emplaced in a relatively short period at ca. 1.93-1.94 Ga and were immediately metamorphosed at ca. 1.91-1.92 Ga. In situ zircon Hf-O isotopic data suggest that both mantle-derived juvenile materials and supracrustal rocks (i.e., the Xingditag Group) were involved in magma genesis. The sodic trondhjemite and tonalite were generated by partial melting of newly underplated mafic lower crust originating from both depleted and relatively enriched mantle, with some assimilation of sedimentary materials. In contrast, the other (mostly high-K) granitoids (monzo granite, quartz diorite/quartz monzonite, and garnetbearing grano diorite) were produced by partial melting of metasedimentary rocks due to intrusion of, and mixing with, variable amounts of mantle-derived mafic magmas, suggesting that these granitoids may also have recorded substantial crustal growth. These petrogenetic interpretations imply that most granitoids in the study area were a result of synchronous crustal growth and reworking, which must be carefully considered in models of continental growth. The adakitic trondhjemite and tonalite have high Sr/Y, La/Yb, Gd/Yb, Nb/Ta, and Zr/Sm ratios, suggesting partial melting with a rutile eclogite residue and implying significant crustal thickening (>50 km). This tectonothermal event most likely occurred in an Andean-type continental arc and was followed by continental collision at ca. 1.85 Ga along the newly recognized late Paleoproterozoic North Tarim orogen. Such an accretion-tocollisional orogen implies an interior position of this area within the Columbia (or Nuna) supercontinent. Based on geological correlations, a Tarim-North China connection is suggested for Columbia reconstruction.